Mawaddah Residential College for UMP students with the concept of waqf - Mimi Rabita, Abdul Wahit (2021)
PEKAN, 11 March 2021 - Universiti Malaysia Pahang (UMP) will have student accommodation with a waqf concept when the Mawaddah Residential College, which is established to provide accommodation to students among the orphans or zakat beneficiaries (asnaf), is fully completed early next year.